Stability of Rectangular Connection Elements - Dowswell, Bo (Engineering Journal, 2016)
Connection elements are commonly designed using the flexural buckling and lateral-torsional buckling provisions in AISC Specification Sections E3 and F11, respectively, as well as the combined-load requirements of Section H1. Because these provisions were developed for main members, their accuracy for designing connection elements is questionable. The factors affecting the stability of connection elements are discussed, with an emphasis on the differences between main members and connection elements. The available experimental and theoretical results are compared to the AISC Specification equations. Where required, new equations are derived, and practical design solutions are recommended. Recommendations are also made for connection elements subjected to combined axial and flexural loads. Examples are provided to illustrate the proposed design procedures for double-coped beams.